The Influence of Clan Chess-Based Work Culture, Work Discipline, and Employee Compensation on Work Productivity at BKPSDM Buleleng Regency - Dewi, Komang Trisna Sari; Dewi, Kadek Ria Padma (Moneter: Jurnal Keuangan dan Perbankan, 2025)
The purpose of this study isi to analyze the influence of Catur Marga-basedi worki culture, work discipline, andi employeei compensationi oni worki productivity at thei Bulelengi Regency Personneli andi Human Resources Development Agency. Thisi research is a quantitativei researchi with a causal associative approach. Thei populationi ini thei study wasi 89 ASN employees with the purposivei samplingi method of the researchi sample was 43 ASN employees. Thei researchi instrumenti usedi ai questionnairei withi a data analysisi techniquei usingi multiplei linear regressioni analysis. Thei results ofi thei study stated thati Catur Marga-based work culturei hasi ai positive andi significanti effect oni work productivity, worki disciplinei hasi ai positive and significant effect on work productivity, andi employee compensationi has ai positivei and significanti effecti oni work productivity.